1991
DOI: 10.1093/ajcn/53.5.1191
|View full text |Cite
|
Sign up to set email alerts
|

Dietary treatment for familial hypercholesterolemia—differential effects of dietary soy protein according to the apolipoprotein E phenotypes

Abstract: Familial hypercholesterolemia, one form of type IIa hyperlipidemia, usually responds poorly to standard low-lipid diets. To define the responsiveness to a soy-protein diet in this disease, one homozygous and twenty heterozygous type IIa patients were submitted to a 4-wk traditional hypocholesterolemic diet followed by 4 wk in which animal protein was substituted with texturized soy protein. Soy was then withdrawn for a further 4 wk. No significant changes in plasma lipids were observed during low-lipid diets. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 25 publications
0
20
1
2
Order By: Relevance
“…These factors are all known to affect the metabolism of TG-rich lipoproteins. Previous studies also reported that soybean protein decreased the fasting plasma lipid concentration when lipids levels of subjects were elevated by dietary or genetic factors, or by chronic diseases (high fat intake, familial hypercholesterolemia (17,33), renal disease (34), nephrotic syndrome (34,35)). In this study, however, all the subjects were normolipidemic, and the fasting levels of plasma lipids and apolipo proteins were not affected by SPI or casein intake.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…These factors are all known to affect the metabolism of TG-rich lipoproteins. Previous studies also reported that soybean protein decreased the fasting plasma lipid concentration when lipids levels of subjects were elevated by dietary or genetic factors, or by chronic diseases (high fat intake, familial hypercholesterolemia (17,33), renal disease (34), nephrotic syndrome (34,35)). In this study, however, all the subjects were normolipidemic, and the fasting levels of plasma lipids and apolipo proteins were not affected by SPI or casein intake.…”
Section: Discussionmentioning
confidence: 88%
“…Decreased levels of TC, TG and LDL-C are believed to be associated with a decreased risk of CAD. Several mechanisms have been proposed whereby soybean protein reduces plasma TC: (1) it raises LDL receptor activity (14)(15)(16)(17); (2) it reduces intestinal bile acid and cholesterol absorption (18)(19)(20); (3) it raises lipoprotein lipase (LPL) activity (21); and (4) it alters insulin levels (22). In the postprandial state, intestine-derived chylomicrons are hydrolyzed by LPL and converted to cholesterol-rich chylomicron remnants .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in 1980, 22.5% of older men and 21.5% of older women (9.5% and 8.3%, respectively, after NEP in 1986 ± 1989) had a multiple de®cit in food intake of calcium, vitamin D and magnesium. These daily intakes were calculated from data obtained by the 7-day questionnaires: this dietary record seems to be accurate as long as the subjects are willing to cooperate, as also shown in some controlled clinical trials (Gaddi et al, 1990). It meets the characteristics required by the nutritional habit survey in populations (Dwyer, 1994), particularly for the simplicity of the descriptive part and the accuracy of the quantitative part, avoiding typical disadvantages related ot the use of a 24 h recall (day-to-day variations of food consumption and other bias sources; Dwyer, 1994;Bingham et al, 1988;Block, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…. Antonio gaddi et al 23 showed that Soy protein decreased TC (-20.8%) and LDL (-25.8%) levels in patients suffering from FH. But Cochrane reviews stated that, no conclusions can be made about the effectiveness of a cholesterol-lowering diet, or any of the other dietary interventions suggested for FH, due to the lack of adequate data.…”
Section: Diet and Lifestylementioning
confidence: 99%